Sources for Christian Bioethics: The Orthodox Discourse on Sin - Tarabrin, Roman (Christian bioethics, 2025)
The article discusses ways of developing bioethical guidance in the Orthodox Christian discourse. Here, "ethical" refers to what contributes to holiness, "un-ethical" refers to sin as what hinders man’s foundational calling to holiness. To explore the development of guidance for emerging bioethical issues, we use the "therapeutic" understanding of treatment for sin in two senses. (1) It refers to the spiritual means provided by the "hospital" of the Orthodox Church for healing the fallenness of human nature in general; and (2) it helps identify in particular cases both what counts as transgression of unconditional boundaries (defining what is illicit for everyone) and what is advisable in order to help particular persons to choose rightly within the area of the "more or less licit" (or "permissible"). Sources of the Orthodox faith that frame the general understanding of the boundaries between the permissible and the impermissible reflect the work of the Holy Spirit in the Church framing her Sacred (Holy) Tradition. In Holy Tradition, prayers, as communion with God, occupy a central position. This is why Orthodox moral reasoning, and thus also Orthodox bioethics, takes the form of liturgical bioethics. Penalties of excommunication determine hard boundaries that believers should not overstep: when crossing such boundaries, they enter on a spiritually dangerous path that completely distracts them away from God. Many minor sins, by contrast, have not been codified in Canons. They are not taken to remove the sinner completely from contact with the Lord. Within this realm of actions, it depends on a person’s spiritual maturity whether such actions are classified as sinful. Thus, an act can be counted merely as a small offense if committed by a beginner, while that same act can become a grave sin for an advanced believer. Due to acceleration of the technological progress, Orthodox recourse to Holy Tradition encounters ever-new challenges. There are bioethical issues that had not surfaced at the time of the Fathers of the Church. Today, Bishops gathered at a local council can supply the guidance lacking on a newly emerging bioethical problem. Even if ratified only by such local councils, the resulting decrees can also be regarded as the expression of the Holy Spirit working within a local Church and conveying His guidance. The article illustrates this source of Christian bioethics by reference to how the Russian Orthodox Church orients and develops its position on the ethics of reproductive technologies.